EDUKASI PENCEGAHAN DAN PENANGANAN STUNTING: education on preventing and handling stunting - Susanti, Linros; Ika, Hendrika (Jurnal Pengabdian pada Masyarakat Kepulauan Lahan Kering, 2024)
Abstract The first thousand days of life (1000 HPK) are very important in human growth and development. About 80% of the development of the brain and body organs occurs during the golden period (1000 HPK). Missing the opportunity to grow optimally during this period can cause stunting with long-lasting impacts. Education for mothers of toddlers includes improving nutrition, monitoring routine growth every month, and monitoring development regularly at least once every 3 months. The activity was carried out with the aim of increasing community knowledge about stunting in Oesusu Village, Kupang Regency in September 2023. Implementation used the "group counseling" method. Where, all communities are given counseling with the aim that they can understand, change their daily culture regarding the problem of stunting and all the causes and impacts related to the problem of stunting. The evaluation process was carried out before and after the activity to measure the abilities and changes in attitudes of 50 participants consisting of family mothers, posyandu cadres, and Oesusu Village officials, Kupang Regency regarding the counseling material. The pre-tesresults found that the majority (89.8%) of the counseling participants did not understand stunting, its causal factors and impact on children's growth and the quality of human resources. However, after confirmation of the results of the counseling, it was discovered that 100% of the counseling participants could understand and be able to answer questions about the counseling material. This means that it is still very important to continue providing education to the community, cadres and village officials in order to support efforts to accelerate stunting reduction. Keywords: community participation, clean and healthy living practices, prevention and management of stunting, Oesusu village, Kupang district